Visual Media and Religious Perception: A Media Anthropological Study of The Passion of the Christ at S Church - XIONG, Wei (Journal of Research for Christianity in China (JRCC), 2025)
In this study, I was doing fieldwork in S parishes which belongs to the Roman Catholic Diocese of Yichang .I used the participant observation and in-depth interviews and other qualitative research methods, from the sight of the media anthropology, through the show of "Passion of the Christ" , explored the film how impact on local propagation conditions and cognitive structures , as well as the relationship between cognitive image media and faith in the presentation of local social and cultural context.